High density tungsten gadolinium borate glasses doped with Eu3+ ion for photonic and scintillator applications - N. Wantana (2020)
© 2020 Elsevier Ltd The melt quenching technique used to prepare tungsten gadolinium borate (Eu: WGdB) glasses doped with different concentrations of Eu3+ ions. The structural and spectroscopic analysis have been carried out by density, molar volume, X-ray absorption spectroscopy (XAS), UV-VIS-NIR absorption, excitation, emission spectra and decay time measurements. The glasses containing WO3 exhibit a high density of more than 6.00 g/cm3 and performs the enhanced compaction with increment of Eu2O3 content. The average coordination number of oxygen surrounding Eu3+ is 6.000 and the average bond length between Eu3+ and oxygen is 2.3740 Å. Eu3+ in glass absorb photons in visible light and near infrared region. The strong reddish orange emission around 613 nm via 5D0→7F2 radiation transition of Eu3+ was generated under different types of excitation such as ultraviolet, visible light and X-ray. The Gd3+ - Eu3+ energy transfer has an important role for strong reddish orange emission under 275 nm excitation. The Judd-Ofelt (J-O) theory was used to predict the radiative properties for the Eu3+ ion emission levels. The decay curves of the 5D0 levels exhibit single exponential nature with a lifetime of millisecond order. The high stimulated emission cross-section and intense emission with 613 nm wavelength suggests that the present Eu-WGdB glasses could be useful for the solid-state laser, display devices and radiation detecting material applications.